Early Eocene 40Ar/39Ar Age for the Pampa de Jones plant, Frog, and Insect Biota (Huitrera Formation, Neuquén Province, Patagonia, Argentina) - Wilf, Peter (2010)
The Pampa de Jones fossil site, a stratigraphically isolated roadcut near the northeastern shore of Nahuel Huapi Lake in Neuquén Province, Argentina, holds a rich fossil biota including a macroflora, a microflora, insects, and most famously, an ontogenetic series of pipid frogs. The site exposes tuffaceous mudstone and sandstone beds of probable lacustrine origin, considered to belong to the volcanic Huitrera Formation. However, there have been no reliable age constraints for the fossil assemblage. We undertook laser fusion analyses of sanidine and biotite crystals occurring in a tuff layer found 4.4 m above the main fossil horizon. Twentyeight sanidine crystals yielded an 40ArZ39Ar age of 54.24 ± 0.45 Ma that is preferred over our biotite age of 53.64 ± 0.35 Ma. Pampa de Jones is thus the oldest well-dated Eocene fossil site in Patagonia, predating two other recently 40Ar/39Ar-dated sites: Laguna del Hunco (51.91 ± 0.22 Ma) and Rio Pichileufu (47.46 ± 0.05 Ma). The improved age control makes possible a finer scale of evolutionary hypothesis testing and turnover analysis in the region. The age is concordant with the site's placement in the Huitrera Formation and a depositional origin related to Early Paleogene arc volcanism, and it correlates to an interval of significant climate fluctuations following the Paleocene-Eocene boundary. ©Asociación Paleontológica Argentina.